Essential Role of Chromatin Remodeling Protein Bptf in Early Mouse Embryos and Embryonic Stem Cells - Landry, Joseph; Sharov, Alexei A.; Piao, Yulan; Sharova, Lioudmila V.; Xiao, Hua; Southon, Eileen; Matta, Jennifer; Tessarollo, Lino; Zhang, Ying E.; Ko, Minoru S. H.; Kuehn, Michael R.; Yamaguchi, Terry P.; et al. (PLoS genetics, 2008)
We have characterized the biological functions of the chromatin remodeling protein Bptf (Bromodomain PHD-finger Transcription Factor), the largest subunit of NURF (Nucleosome Remodeling Factor) in a mammal. Bptf mutants manifest growth defects at the post-implantation stage and are reabsorbed by E8.5. Histological analyses of lineage markers show that Bptf(-/-) embryos implant but fail to establish a functional distal visceral endoderm. Microarray analysis at early stages of differentiation has identified Bptf-dependent gene targets including homeobox transcriptions factors and genes essential for the development of ectoderm, mesoderm, and both definitive and visceral endoderm. Differentiation of Bptf(-/-) embryonic stem cell lines into embryoid bodies revealed its requirement for development of mesoderm, endoderm, and ectoderm tissue lineages, and uncovered many genes whose activation or repression are Bptf-dependent. We also provide functional and physical links between the Bptf-containing NURF complex and the Smad transcription factors. These results suggest that Bptf may co-regulate some gene targets of this pathway, which is essential for establishment of the visceral endoderm. We conclude that Bptf likely regulates genes and signaling pathways essential for the development of key tissues of the early mouse embryo.